Accelerators of Osteogenesis by Recombinant Human Bone Morphogenetic Protein-2 - Yasunori Okubo; Kenji Kusumoto; Kazuhisa Bessho (AboutScience Srl, 2007)
Bone morphogenetic protein (BMP) appears to be one of the most promising cytokine and for clinical use in reconstructive surgery for bony defects and augmentation. To evaluate the effect of basic fibroblast growth factor (bFGF), FK506, elcatonin, and hyperbaric oxygenation (HBO) on osteoinduction by recombinant human bone morphogenetic protein-2 (rhBMP-2), 2 or 5 μg of rhBMP-2 was implanted into intramuscular sites of rats. At 21 days after implantation, the osteoinductive activity in the treatment group and control group was compared radiographically, biochemically, and histologically. The amount of new bone in the treatment group was significantly greater than that in the control group. The alkaline phosphatase activity and calcium content in the treatment group were significantly higher than those in the control group. These results suggest that bFGF, FK506, elcatonin, and HBO accelerated the activity and rate of osteoinduction by rhBMP2. These results may be useful when BMP is applied clinically in near future.